2019
DOI: 10.1126/science.aaw7317
|View full text |Cite
|
Sign up to set email alerts
|

Conservation, acquisition, and functional impact of sex-biased gene expression in mammals

Abstract: Sex differences abound in human health and disease, as they do in other mammals used as models. The extent to which sex differences are conserved at the molecular level across species and tissues is unknown. We surveyed sex differences in gene expression in human, macaque, mouse, rat, and dog, across 12 tissues. In each tissue, we identified hundreds of genes with conserved sex-biased expression—findings that, combined with genomic analyses of human height, explain ~12% of the difference in height between fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
213
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(224 citation statements)
references
References 111 publications
10
213
0
1
Order By: Relevance
“…Using RNA-seq data from 12 male mouse tissues (Naqvi et al, 2019), we identified testisspecific genes (Table S2) and confirmed that Dazl expression is testis-specific, as previously described (Nicholls et al, 2019b). We found that testis-specific factors comprised 5.3% of the 10 genes expressed in undifferentiated spermatogonia but only 2.7% of DAZL targets, representing a depletion of testis-specific factors among DAZL targets (one-tailed hypergeometric test; P = 1.78 x 10 -13 ; Figure 3C).…”
Section: Dazl Interacts With Broadly Expressed Dosage-sensitive Regusupporting
confidence: 83%
“…Using RNA-seq data from 12 male mouse tissues (Naqvi et al, 2019), we identified testisspecific genes (Table S2) and confirmed that Dazl expression is testis-specific, as previously described (Nicholls et al, 2019b). We found that testis-specific factors comprised 5.3% of the 10 genes expressed in undifferentiated spermatogonia but only 2.7% of DAZL targets, representing a depletion of testis-specific factors among DAZL targets (one-tailed hypergeometric test; P = 1.78 x 10 -13 ; Figure 3C).…”
Section: Dazl Interacts With Broadly Expressed Dosage-sensitive Regusupporting
confidence: 83%
“…Connectivity has been shown to be different in the sexes in the frontal cortex, whereas neuronal activity differs in the hippocampus, hypothalamus, frontal cortex, amygdala, and pituitary gland . Cell composition of the frontal cortex, amygdala, and hypothalamus and the transcriptional profile of the pituitary gland, frontal cortex, hippocampus, hypothalamus, and amygdala, were also found to be sex specific…”
Section: Introductionmentioning
confidence: 98%
“…15,16 Similarly, other regions, such as the hippocampus and the amygdala, have higher activation for women in response to negative emotions. 17,18 Many of these regions also show sex dimorphism in structure, [19][20][21][22][23][24][25][26][27] connectivity, 28 cell composition, 29,30 and transcriptional profile [31][32][33][34][35][36] (Figure 1).…”
mentioning
confidence: 99%
“…Second, a recent study (Naqvi et al, 2019) demonstrates that most sex bias in gene expression has arisen since the last common ancestor of boroeutherian mammals (including mouse, rat, dog, macaque, and human), resulting in inadequate representation of sexual dimorphism in any non-human model organism; and third, current animal models of SCZ and BD do not faithfully represent human pathology, showing no predictive power for clinical efficacy of therapeutics (Jones et al, 2011). Additionally, the resolution of differential expression analysis in sequencing is much higher in a homogeneous cell population such as neuronal cell culture, as sexual dimorphism can also manifest in distinct tissue composition (Naqvi et al, 2019). However, this choice also entails limitations: Although very similar, LA-N-2 and LA-N-5 are immortalized cells derived from two distinct donating individuals, which must be considered when interpreting sexual dimorphisms based on their total transcriptional divergence.…”
Section: Limitationsmentioning
confidence: 96%
“…First, implementation of cholinergic differentiation in the brain of a living animal is not straightforward, and individual types of cholinergic neurons are quantitatively inferior to supporting cells in the cortex (von Engelhardt et al, 2007). Second, a recent study (Naqvi et al, 2019) demonstrates that most sex bias in gene expression has arisen since the last common ancestor of boroeutherian mammals (including mouse, rat, dog, macaque, and human), resulting in inadequate representation of sexual dimorphism in any non-human model organism; and third, current animal models of SCZ and BD do not faithfully represent human pathology, showing no predictive power for clinical efficacy of therapeutics (Jones et al, 2011). Additionally, the resolution of differential expression analysis in sequencing is much higher in a homogeneous cell population such as neuronal cell culture, as sexual dimorphism can also manifest in distinct tissue composition (Naqvi et al, 2019).…”
Section: Limitationsmentioning
confidence: 99%